2013
DOI: 10.1093/gerona/glt118
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Poor Quality Drug Prescribing in Older Individuals: A Nationwide Report From the Italian Medicines Agency (AIFA)

Abstract: These results confirm the high frequency of suboptimal drug prescribing in older adults, using a database that covers the whole Italian population. In general, this descriptive study may help in prioritizing strategies aimed at improving the quality of prescribing in elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 35 publications
5
50
1
3
Order By: Relevance
“…In an extensive Italian study conducted by AIFA (Italian Medicines Agency), the number of medications ≥5 per day was 69.1% in the cohort from 75 to 84 years old and 66.7% in the group over 85, whereas constant use of ACEi/ARBs plus aldosterone-antagonists plus non-steroidal anti-inflammatory drugs (NSAIDs) was, respectively, 0.9 and 0.4% [19].…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive Italian study conducted by AIFA (Italian Medicines Agency), the number of medications ≥5 per day was 69.1% in the cohort from 75 to 84 years old and 66.7% in the group over 85, whereas constant use of ACEi/ARBs plus aldosterone-antagonists plus non-steroidal anti-inflammatory drugs (NSAIDs) was, respectively, 0.9 and 0.4% [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that one-fifth of adult patients are treated with polypharmacy (five or more drugs) and the prevalence of this phenomenon in the elderly is higher, ranging from 30% to 70%, even reaching 90% in residents of residential aged care facilities [1][2][3][4]. Polypharmacy in the elderly increases the risk of adverse reactions, inappropriate prescriptions, drug interactions, number of hospitalizations, costs, and even death [5].…”
Section: Deprescriptions; Polypharmacy; Pharmacovigilance; Pharmacoepmentioning
confidence: 99%
“…Data from the Italian Agency of Medicine showed that over 6,000,000 (50%) of Italians aged 65 or more chronically receive 5-9 drugs, whereas almost 1,400,000 of them are prescribed 10 or more [1] . Polypharmacy mainly derives from the application of disease-specific guidelines, targeting disease-specific goals, in persons affected by multiple chronic diseases [2] .…”
Section: Introductionmentioning
confidence: 99%